Rancang Bangun Sistem Pakar untuk Mendiagnosa Kerusakan Handphone Android dengan Metode Forward Chaining - Safira Agustina; Hetty Rohayani; Noneng Marthiawati; Kevin Kurniawansyah (Journal of Informatics Management and Information Technology, 2023)
Expert systems are computer-based systems that use knowledge, facts, and reasoning techniques to solve problems that usually can only be solved by an expert in a particular field. The purpose of making an expert system for diagnosing damage to Android cellphones is to provide knowledge and information in repairing Android cellphones based on the type and characteristics of the damage that has occurred. The method used in this study is to use the forward chaining method, which aims to determine the type of damage experienced. The input needed is to choose a choice of questions regarding the symptoms that occur. The result of using the forward chaining method is the output solution in repairing damage to Android cellphones. And an expert system for damage to Android cellphones can help novice users or technicians to be able to find out precisely about the damage experienced by Android cellphones based on a selection of damage symptoms, so that repairs can be carried out quickly and precisely.